COMBINING THE ACTION OF THE PENDULUM APPLIANCE WITH RAPID PALATAL EXPANSION - Greta Yordanova; Martin Mladenov; Gergana Gurgurova (Peytchinski Publishing, 2017)
The borderline indications between extraction and non-extraction treatment are not well defined in the orthodontics. The sagittal tooth movement for lengthening the tooth arch and space gaining should be considered with several aspects. Many authors have suggested appliances with combined action in several planes. In our opinion, it is very hard to achieve transverse dimension and apply well balanced sagittal force with one appliance. Our aim is to define the gained space in the dental arch using two successive appliances: RME and M-pendulum modified by us for remaining the transverse arch dimensions. We suggest a modification of the appliance remaining the achieved transversal dimension during the molar distal movement. We added an additional wire grill to the classic design of the M-Pendulum appliance in 14 patients. The length of the dental arch can be increased with expansion (RME), molar rotation correction with 2mm, distal movement of the upper molars 3-4mm, protrusion of the frontal teeth 1.5mm, slenderizing 4mm. The sum of all these methods reaches the amount of the dimension of the space gained with the extraction of two premolars. A single appliance cannot achieve the full amount of tooth movement. The modified by us M-pendulum perfectly keeps the achieved transverse dimension right after the RME and achieves sagittal movement of the upper molars.